Factors Influencing Dietary protein sources in the PREMIER trial population - Lin, Pao-Hwa (2010)
Previous research suggests that protein intake, particularly plant protein, may benefit blood pressure (BP) control. However, very little has been published regarding protein sources in diets of the US adults and factors influencing these choices. The purpose of this report is to describe specific sources of animal and plant proteins in diets of PREMIER clinical trial participants at baseline and how the PREMIER intervention, along with participant demographics, affected protein sources. Adult participants (n=809) who completed the 18-month PREMIER lifestyle intervention trial and had at least one diet recall at each of three study visits were included. Participants were recruited from four clinical centers in the Eastern, Southern and Northeastern regions of US. The PREMIER trial, conducted from 1999 to 2002, compared the impact on BP of two structured behavioral interventions focusing on the traditional lifestyle modifications for BP control with or without the Dietary Approaches to Stop Hypertension (DASH) dietary pattern. Protein sources were assessed by two unannounced 24 hour recalls at each of three study visits. Differences in protein sources were mainly related to participant demographics, with relatively moderate impact of the intervention. The top four protein sources for all the study participants were poultry, dairy, refined grains and beef, each contributing approximately 10–17% in descending order to the total protein intake at baseline. Animal and plant protein each comprised approximately 66% and 34%, respectively, to the total daily protein intake at baseline and such overall contribution pattern remained relatively constant over time. However, gender, race, age and body weight status all influenced contribution patterns from different food groups significantly. These influences significantly impact choice and are essential elements to consider when designing intervention programs to alter protein contributions from animal versus plant sources.